Forecasts for warm dark matter from photometric galaxy surveys - Martins, Jéssica S. [UNESP]; Rosenfeld, Rogerio [UNESP]; Sobreira, Flavia (Oxford University Press (OUP), 2018)
We present a Fisher matrix forecast for the sensitivity on the mass of a thermal warm dark matter (WDM) particle from current (DES-like) and future (LSST-like) photometric galaxy surveys using the galaxy angular power spectrum. We model the non-linear clustering using a modified Halo Model proposed to account for WDM effects. We estimate that from this observable alone a lower bound of mwdm > 647 eV (mwdm > 126 eV) for the LSST (DES) case could be obtained.
Keywords: Dark matter; Large-scale structure of Universe; Surveys